Dangerous Liaisons? Governments, companies and Internet governance - Francesca Musiani (Internet Policy Review, 2013)
Private actors in the information technology sector are currently playing an increasingly important role in content mediation, as well as in regulation of online forms of expression, with implications for both internet rights and economic freedom. The "privatisation of internet governance" (DeNardis, 2010), is not a new dynamic; however, in a scenario in which users are taking advantage of increasingly sophisticated technology, the centralisation and concentration characterising today's most widespread internet services are contributing to the accentuation of this tendency. The 'inherently political' qualities of search engine algorithm development, video content removals, blocking of domain names – actions that originate and rest with the private sector's handling of the internet's infrastructure – should not be neglected in our assessment of the field of internet governance today.
Keywords: 300; Internet governance; Regulation; Privatisation; Private sector; Infrastructure; Infomediary